Agricultural Nisab Measurement for Zakat Assessment - Dg Nooremah Ag Said; Rose Irnawaty Ibrahim; Azman Ab Rahman; Hafidzi Hamdan (Lembaga Zakat Negeri Kedah, 2024)
Volume: 5 Issues: 1 [March, 2023] pp.92-105]